Description of Early Childhood Dhuha Prayer Habituation Activities in Early Childhood Education Units - Saniyya Putri Hendrayana; Irma Yuliantina (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2024)
Religious education in early childhood is an essential guide for getting closer to Allah and behaving according to the social norms that are in place. Dhuha prayer habits is performed every morning at Aditya Playgroup, Karawang. However, in implementation, some children are not yet stable and consistent so they still need teacher guidance. This research aims to describe early childhood Dhuha prayer habits in early childhood education units. This research was conducted using qualitative phenomenological methods. Data collection techniques use interviews, observation and documentation. There were 4 informants consisting of the principal, class teacher and parents. The research results showed that of the 23 children who were accustomed to Dhuha prayer activities, 21 were accustomed to performing Dhuha prayers at school and at home. The Dhuha prayer habituation activities at Aditya Playgroup are following the Dhuha prayer procedures. Children also learn the procedures for ablution by singing ablution claps. Children can also master reading and praying the Dhuha prayer without memorizing, so getting used to the Dhuha prayer can be said to be successful in building good habits in children.